2013
DOI: 10.1186/cc13026
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of critically ill patients in intensive care units: a population-based observational study

Abstract: IntroductionEpidemiologic assessment of critically ill people in Intensive Care Units (ICUs) is needed to ensure the health care system can meet current and future needs. However, few such studies have been published.MethodsPopulation-based analysis of all adult ICU care in the Canadian province of Manitoba, 1999 to 2007, using administrative data. We calculated age-adjusted rates and trends of ICU care, overall and subdivided by age, sex and income.ResultsIn 2007, Manitoba had a population of 1.2 million, 118… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 34 publications
6
56
1
6
Order By: Relevance
“…This observation is in line with reports from other studies [5]- [7]. The mean age of the total population was 58.92+13.89 years covering a age ranges from 14 to 102 years while results from different studies revealed lower mean age [5], [8] as well as higher mean age [6], [8], [9]. Table 1 shows that almost fifty three percent of the total population were aged between 40-60 years, 49.61% aged 60years and above and 13.44% between the age group of 20-40 years.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is in line with reports from other studies [5]- [7]. The mean age of the total population was 58.92+13.89 years covering a age ranges from 14 to 102 years while results from different studies revealed lower mean age [5], [8] as well as higher mean age [6], [8], [9]. Table 1 shows that almost fifty three percent of the total population were aged between 40-60 years, 49.61% aged 60years and above and 13.44% between the age group of 20-40 years.…”
Section: Resultssupporting
confidence: 91%
“…The length of stay of admitted cases in ICUs was evaluated from the day admitted to ICUs to the discharge day from ICUs (Figure 1) and it was found that majority (54.43%) of patient admitted to JMCH stayed for a duration of 10-15 days while 66.13 per cent of patients from private hospital (JCMC) stayed 6-10 days being a mean of 8.34+2.5 days for the whole population. The mean LOS for individuals ICUs episodes in different studies reveals comparatively lower mean Los range of 4to 67 days [9], [11] [7]. There were no significant relation between the disease diagnosed and length of stay(p=0.05).…”
Section: Resultsmentioning
confidence: 99%
“…[1] Approximately 10% of patients discharged from the ICU require readmission during the same hospital stay. [2] Readmission exposes patients to increased risks, as transfers between healthcare professionals have been linked to an increased rate of adverse events, higher mortality, and longer hospital stays.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Studi epidemiologi pasien sakit kritis yang berbasis populasi yang dilakukan di Canada menyebutkan bahwa angka kejadian sakit kritis lebih banyak terjadi pada laki laki daripada perempuan tetapi penolakan terhadap perawatan di ICU dan tata laksanan agresif lebih banyak terjadi pada perempuan. 7 Angka mortalitas pada studi ini adalah 68,6%, dengan faktor risiko penyakit terbanyak adalah sepsis berat (78,9%). Angka mortalitas pada studi ini sesuai dengan beberapa studi mortalitas kandidiasis invasif, dimana angka mortalitas berkisar antara 30 -70%.…”
Section: Diskusiunclassified